Evaluación clínica del ionómero de vidrio modificado de restauración tipo dos y un composite bulk fill en restauraciones clase uno en dientes deciduos - Aragundi Castro, Carlos Alberto (2017)
At present it is extremely important to know what dental materials provide a guarantee in its application and functionality, within the Pediatric Dentistry this aspect is one of the main challenges when attending the child, are optimizing materials such as glass ionomer , whose main benefit is the release of fluoride, are being developed composites of application in block of up to 4mm as the Bulk Fill that modifies the conventional protocols, all these advances are with the purpose of giving the professional the best option at the time of dental care. The objective of this study was the Clinical Evaluation of Modified Glass Ionomer Restoration Type two and a Composite Bulk Fill in class one restorations in deciduous teeth. Materials and Methods: The study involved 16 children, who compared 32 deciduous molars, which were restored with modified glass Ionomer of restoration type two (50 percent) group A and composite Bulk Fill (50 percent) group B, was assessed between the two Materials 3 aspects, working time, marginal wear, and color change. Results: when comparing the materials in the working time group B presented less time than Group A being statistically significant, there was no difference in relation to the marginal wear in both groups A and B, but if there was a significant difference in relation to color In group B, because the Bulk Fill resin was more translucent than the ionomer, therefore it was concluded that clinically the two materials are useful, effective to be used in restorations in children at the time of dental care.